Treatment of Tunneled Dialysis Catheter Malfunction: Revision versus Exchange. Issue 4 (July 2016) - Wang, Jackson; Nguyen, Tuan A.; Chin, Andrew I.; Ross, Jamie L.
Introduction: Exchange procedures involve tunneled dialysis catheter (TDC) removal and exchange over a wire, using the same exit site and venotomy site. Diagnostic imaging or intervention was generally not performed in exchange procedures. Revision procedures involve placement of new TDC using the previous venotomy site and a new tunnel and exit site. The majority of revisions usually include diagnostic imaging and intervention in the central circulation if needed. Methods: A retrospective single review of 70 patients who underwent 97 TDC replacements from 2010 to early 2012 because of catheter malfunction was evaluated for either infection or malfunction within 30 days of the procedure. Results: There were 41 exchanges and 56 revisions out of the 97 procedures performed. There were eight infections (documented by positive blood culture) in the exchanges (19.5%) and one in the revision group (1.8%). The need for an additional procedure due to malfunction was 10 in the exchange (24.4%) and 10 (17.8%) in the revision group. Conclusions: Revision is a clearly superior procedure with regard to infection and more data need to be gathered as to whether it will decrease repeat procedures.